2020
DOI: 10.3389/fmicb.2020.00745
|View full text |Cite
|
Sign up to set email alerts
|

Gross N2O Production Process, Not Consumption, Determines the Temperature Sensitivity of Net N2O Emission in Arable Soil Subject to Different Long-Term Fertilization Practices

Abstract: Chronic amendment of agricultural soil with synthetic nitrogen fertilization and/or livestock manure has been demonstrated to enhance the feedback intensity of net N 2 O emission to temperature variation (i.e., temperature sensitivity, TS). Yet few studies have explored the relevance of changes in underlying gross N 2 O production and consumption processes toward explaining this phenomenon, in particular for the latter. Furthermore, the microbe-based mechanisms associated with the variation of N 2 O consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Semedo et al showed that tetracycline exposure increased N 2 O release in soil by simultaneously enhancing N 2 O production and inhibiting N 2 O reduction. We applied C 2 H 2 inhibition to discriminate between gross N 2 O production and consumption processes, , and found different results. ENR inhibited both gross N 2 O production and consumption processes, particularly in the bare soil (Figure ), which was likely associated with the decrease in almost all the detectable functional genes involved in nitrification and denitrification after elevating the ENR concentration (Figure a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Semedo et al showed that tetracycline exposure increased N 2 O release in soil by simultaneously enhancing N 2 O production and inhibiting N 2 O reduction. We applied C 2 H 2 inhibition to discriminate between gross N 2 O production and consumption processes, , and found different results. ENR inhibited both gross N 2 O production and consumption processes, particularly in the bare soil (Figure ), which was likely associated with the decrease in almost all the detectable functional genes involved in nitrification and denitrification after elevating the ENR concentration (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…A microcosm study was applied to investigate the legacy effect of growing vegetables and ENR treatment on soil and their roles in changing soil N 2 O flux. Gross N 2 O production and consumption rates were determined using the C 2 H 2 inhibition method following the procedure as described by Yin et al Briefly, soil samples collected on days 7 and 44 from the pot experiment were selected for the microcosm study. Three treatments were designed for each soil sample with three replicates, namely, 0 Pa of C 2 H 2 (net N 2 O production), 10 Pa of C 2 H 2 (inhibits nitrification), and 10 kPa of C 2 H 2 (inhibits both nitrification and N 2 O reduction).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most organisms with nosZ clade II are nondenitrifying N 2 O reducers, whereas denitrifiers with N 2 O as an intermediate dominate clade I (Graf et al 2014 ). The soil N 2 O sink capacity has been explained by the abundance and diversity of clade II in arable soils (Jones et al 2014 , Domeignoz-Horta et al 2015 , Yin et al 2020 ) and nondenitrifying N 2 O reducing bacteria can lower the net N 2 O production from soil (Domeignoz-Horta et al 2016 ). Both clades I and II are abundant in soils and rhizosphere (Hallin et al 2018 ), but little is known if plants select for specific N 2 O-reducing communities and the underlying ecological processes governing the colonization of roots by N 2 O-reducers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a higher N 2 Oi (+0.23 ± 0.17 and +0.19 ± 0.24 higher N 2 Oi in maize and S5). This suggests that in both systems, gross N 2 O production exceeds consumption at high WFPS, probably due to high NO − 3 availability (Yin et al, 2020). Although WFPS was 79.5 ± 3.2% and 84 ± 3.3% in cup plant and maize soils, respectively, which is at the upper limit of the optimum range (70%-80% WFPS) for most soils for N 2 O formation during denitrification (Butterbach-Bahl et al, 2013), the N 2 Oi results implied that soil moisture in the high WFPS treatments was, in fact, not above optimum conditions for N 2 O formation.…”
Section: Comparison With Field and Laboratory Studiesmentioning
confidence: 94%